Teknik Soringja Sebagai Peningkatan Aktivitas Belajar IPA Materi Biologi - Yusro, Usrotun Mursidah (widiyanto, 2016)
This study aims to improve the ability to solve problems of material science Biology 9F grade students of SMP 2 Undaan Kudus 2011/2012 through Soringja techniques. Soringja technique is learning techniques to determine the ideas about the main steps, summarize and determine the answer. The research was carried out in three cycles with the stages of planning, action, observation and reflection in February-September 2012 from the initial observation to reporting. Data taken in this research is student activities and student learning outcomes. Sources of data obtained from investigators, collaborators, students and related documentation. Data collection through testing, observation and interviews. The results of this study gained an average score of achievement of student activity and learning outcomes of students has increased from previous cycles. It can be concluded that Soringja techniques can improve the ability to solve problems UN Biological material IPA 2011/2012.Penelitian ini bertujuan untuk meningkatkan kemampuan menyelesaikan soal IPA materi Biologi siswa kelas 9F SMP 2 Undaan Kudus tahun 2011/2012 melalui teknik Soringja. Teknik Soringja adalah teknik pembelajaran dengan langkah utama menentukan ide soal, membuat ringkasan dan menentukan jawaban. Penelitian ini dilaksanakan dalam 3 siklus dengan tahapan perencanaan, tindakan, observasi dan refleksi pada bulan februari-september 2012 mulai dari observasi awal hingga pelaporan. Data yang diambil dalam penelitian ini adalah aktivitas siswa dan hasil belajar siswa. Sumber data diperoleh dari peneliti, kolaborator, siswa dan dokumentasi terkait. Teknik pengumpulan data melalui tes, obervasi dan wawancara. Hasil penelitian ini diperoleh rata-rata skor ketercapaian aktivitas siswa Â dan hasil belajar siswa mengalami peningkatan dari siklus-siklus sebelumnya. Penelitian dapat disimpulkan bahwa teknik Soringja dapat meningkatkan kemampuan menyelesaikan soal UN IPA materi Biologi 2011/2012.